2011
DOI: 10.1128/jcm.01073-11
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Schistosomiasis Due to Schistosoma haematobium Confirmed by PCR Analysis of Brain Specimen

Abstract: The case of a 25-year-old Japanese male who had cerebral schistosomiasis caused by Schistosoma haematobium is reported here. Although serum antibody tests showed a cross-reaction with other helminths and no ova were excreted in urine or feces, the existence of Schistosoma haematobium in the brain was confirmed by PCR analysis. CASE REPORTIn October 2009, a 25-year-old Japanese man was admitted to a local community hospital in Japan with a 1-week history of mild headache and sporadic paraphasia. He had worked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Neuroschistosomiasis is caused by haematogenic invasion of the CNS with eggs from the blood-vessel-dwelling trematode Schistosoma mansoni (Vale et al , 2011), S. japonicum (Ferrari & Moreira, 2011) or S. haematobium (Imai et al , 2011). Other routes of CNS invasion include retrograde venous spread by way of Batons's plexus or migration of worms through the brain (Abdel Razek et al , 2011).…”
Section: Neuroschistosomiasis (Bilharziosis)mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroschistosomiasis is caused by haematogenic invasion of the CNS with eggs from the blood-vessel-dwelling trematode Schistosoma mansoni (Vale et al , 2011), S. japonicum (Ferrari & Moreira, 2011) or S. haematobium (Imai et al , 2011). Other routes of CNS invasion include retrograde venous spread by way of Batons's plexus or migration of worms through the brain (Abdel Razek et al , 2011).…”
Section: Neuroschistosomiasis (Bilharziosis)mentioning
confidence: 99%
“…The CSF may be normal or may show non-specific abnormalities (Ferrari & Moreira, 2011). The diagnosis is confirmed by PCR of the CSF, which may be positive even if serum antibodies are absent or show cross-reaction with other helminthes, and in cases where no ova are excreted via the urine or faeces (Imai et al , 2011). In acute schistosomal encephalopathy, imaging may show cerebral oedema and multiple, small, contrast-enhancing lesions in the frontal, temporal or occipital lobes, or the brainstem (Ferrari & Moreira, 2011).…”
Section: Neuroschistosomiasis (Bilharziosis)mentioning
confidence: 99%
“…specific DNA in CSF compared to serum made such contamination unlikely. Although PCR has previously been used to confirm Schistosoma DNA in brain tissue (Imai et al , 2011), the use of semi-quantification of Schistosoma DNA has not been reported for the confirmation of intrathecal Schistosoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Serological assays are also useful in diagnosing infection by assessing blood serum and cerebrospinal fluid (CSF) to detect antibodies that remain positive for a long time after the resolution of primary infection [96,97]. Eosinophil count and molecular detection of schistosomal DNA by PCR in sera of infected patients may support infection by Schistosoma [98,99]. However, these diagnostic methods cannot assess the severity of the disease and resulting complications as well as clinical signs and symptoms are non-specific and non-reliable in assessing disease severity [100].…”
Section: Schistosoma (Schistosomiasis)mentioning
confidence: 99%